ANALISIS ECONOMIC VALUE ADDED (EVA) UNTUK MENILAI KINERJA KEUANGAN PADA PT. KIMIA FARMA Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rismansyah Rismansyah; M Kurniawan; Rizki Syavitri (Unib Press Universitas Bengkulu, 2021)
This study aims to determine how the financial performance of PT. Kimia Farma Tbk using the Economic Value Added (EVA) analysis method. This research approach is descriptive quantitative by using EVA analysis. The sample of this research is PT. Kimia Farma Tbk during the period 2014-2019. The results showed that the NOPAT value in 2014-2018 increased, but in 2019 the NOPAT value decreased. This factor is caused by the operating profit before tax is smaller than the tax burden. WACC in 2014-2017 experienced an increase due to an increase in the cost of debt and capital. In 2018 and 2019 there was a decrease due to a decrease in the cost of debt and the cost of capital. Capital invested in 2014-2017 increased, while in 2018 and 2019 it decreased due to long-term liabilities that continued to decline. EVA in 2014-2018 has a positive value, meaning that the company is able to provide economic added value for investors. While in 2019 the EVA value was negative, this showed that there was no economic added value to the company.